Inhibition of DDR1‐BCR signalling by nilotinib as a new therapeutic strategy for metastatic colorectal cancer - Jeitany, Maya; Leroy, Cédric; Tosti, Priscillia; Lafitte, Marie; Le Guet, Jordy; Simon, Valérie; Bonenfant, Debora; Robert, Bruno; Grillet, Fanny; Mollevi, Caroline; El Messaoudi, Safia; Otandault, Amaëlle; et al. (EMBO molecular medicine, 2018)
The clinical management of metastatic colorectal cancer (mCRC) faces major challenges. Here, we show that nilotinib, a clinically approved drug for chronic myeloid leukaemia, strongly inhibits human CRC cell invasion in vitro and reduces their metastatic potential in intrasplenic tumour mouse models. Nilotinib acts by inhibiting the kinase activity of DDR1, a receptor tyrosine kinase for collagens, which we identified as a RAS‐independent inducer of CRC metastasis. Using quantitative phosphoproteomics, we identified BCR as a new DDR1 substrate and demonstrated that nilotinib prevents DDR1‐mediated BCR phosphorylation on Tyr177, which is important for maintaining β‐catenin transcriptional activity necessary for tumour cell invasion. DDR1 kinase inhibition also reduced the invasion of patient‐derived metastatic and circulating CRC cell lines. Collectively, our results indicate that the targeting DDR1 kinase activity with nilotinib may be beneficial for patients with mCRC. Synopsis The clinical management of metastatic colorectal cancer (mCRC) faces major challenges. Targeting the receptor for collagens DDR1 by nilotinib inhibits mCRC cells properties and paves the way to a new therapeutic strategy for mCRC. DDR1 tyrosine kinase activity promotes colorectal cancer cell invasion and metastatic properties in nude mice. BCR is a central substrate of DDR1. DDR1 activation maintains a high level of β‐catenin transcriptional activity necessary for cell invasion and metastatic progression. DDR1 pharmacological inhibition by nilotinib inhibits colorectal cancer cell invasion and metastatic properties in nude mice. Nilotinib may be of clinical interest for treatment of metastatic colorectal cancer. Graphical Abstract The clinical management of metastatic colorectal cancer (mCRC) faces major challenges. Targeting the receptor for collagens DDR1 by nilotinib inhibits mCRC cells properties and paves the way to a new therapeutic strategy for mCRC.